Are the effects of psychosocial exposures attributable to confounding? Evidence from a prospective observational study on psychological stress and mortality. Issue 12 (1st December 2001) - Macleod, J; Davey Smith, G; Heslop, P; Metcalfe, C; Carroll, D; Hart, C
Abstract : STUDY OBJECTIVES: To examine the association between perceived psychological stress and cause specific mortality in a population where perceived stress was not associated with material disadvantage. DESIGN: Prospective observational study with follow up of 21 years and repeat screening of half the cohort five years from baseline. Measures included perceived psychological stress, coronary risk factors, and indices of lifecourse socioeconomic position. SETTING: 27 workplaces in Scotland. PARTICIPANTS: 5388 men (mean age 48 years) at first screening and 2595 men at second screening who had complete data on all measures. MAIN OUTCOME MEASURES: Hazard ratios for all cause mortality and mortality from cardiovascular disease (ICD9 390–459), coronary heart disease (ICD9 410–414), smoking related cancers (ICD9 140, 141, 143–9, 150, 157, 160–163, 188 and 189), other cancers (ICD9 140–208 other than smoking related), stroke (ICD9 430–438), respiratory diseases (ICD9 460–519) and alcohol related causes (ICD9 141, 143–6, 148–9, 150, 155, 161, 291, 303, 571 and 800–998). RESULTS: At first screening behavioural risk (higher smoking and alcohol consumption, lower exercise) was positively associated with stress. This relation was less apparent at second screening. Higher stress at first screening showed an apparent protective relation with all cause mortality and with most categories of cause specific mortality. In general, these estimates were attenuated on adjustment for social position. This pattern was also seen in relation to cumulative stress at first and second screening and with stress that increased between first and second screening. The pattern was most striking with regard to smoking related cancers: relative risk high compared with low stress at first screening, age adjusted 0.64 (95% CI 0.42, 0.96), p for trend 0.016, fully adjusted 0.69 (95% CI 0.45, 1.06), p for trend 0.10; high compared with low cumulative stress, age adjusted 0.69 (95% CI 0.44, 1.09), p for trend 0.12, fully adjusted 0.76 (95% CI 0.48, 1.21), p for trend 0.25; increased compared with decreased stress, age adjusted 0.65 (95% CI 0.40, 1.06), p for trend 0.09, fully adjusted 0.65 (95% CI 0.40, 1.06), p for trend 0.08. CONCLUSIONS: This implausible protective relation between higher levels of stress, which were associated with increased smoking, and mortality from smoking related cancers, was probably a product of confounding. Plausible reported associations between psychosocial exposures and disease, in populations where such exposures are associated with material disadvantage, may be similarly produced by confounding, and of no causal significance.